2005
DOI: 10.1345/aph.1e663
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice by Pharmacists: Utilization and Barriers

Abstract: Pharmacist respondents have positive attitudes toward EBM and the application of research findings to practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 10 publications
9
47
0
Order By: Relevance
“…We have also shown that physicians and pharmacists recognized the value of EBP to a similar extent. These findings generally coincide with the results of other studies (28,29). While cost savings in Serbia were forcibly imposed, the effects on clinical decision-making were rather modest.…”
Section: Discussionsupporting
confidence: 89%
“…We have also shown that physicians and pharmacists recognized the value of EBP to a similar extent. These findings generally coincide with the results of other studies (28,29). While cost savings in Serbia were forcibly imposed, the effects on clinical decision-making were rather modest.…”
Section: Discussionsupporting
confidence: 89%
“…These results are similar to the attitudes of pharmacists in Illinois, with 90% of pharmacists reporting a positive or somewhat positive attitude toward evidencebased medicine. 5 Many barriers exist to the implementation of evidence-based practice, including time, access to resources, and attitude. 5,24,25,28 Results of the questionnaire indicate that the attitudes of pharmacy students in this elective course were positive and not likely to be a significant contributing barrier toward evidence-based practice.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was based on an instrument used in a study of physicians' perceptions of evidence-based medicine 24 and adapted to the targeted population of pharmacists. 5 An abbreviated questionnaire was administered to the students. The abbreviated questionnaire consisted of 9 items that assessed the student attitudes toward evidenced-based medicine and self-assessed comfort with technical concepts used in evidence-based medicine.…”
Section: Pre-and Post-elective Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of physicians from 18 different countries, 83% of physicians indicated their understanding of NNT, 22 while studies show that 74-75% of pharmacists understand NNT in the US and Australia. 25,26 While common EBM terms have been penetrating the health profession lexicon around the world, American student pharmacists appear to have greater recognition than those in Japan.…”
Section: -24mentioning
confidence: 99%